1992
DOI: 10.1007/bf02591420
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic and thrombolytic activity of sulodexide in rats

Abstract: We evaluated the ability of sulodexide, an extracted glycosaminoglycan, to prevent thrombus formation and to reduce a stabilized thrombus in a rat venous thrombosis model (vena cava ligature). Injection of sulodexide 10 min before induction of venous stasis, prevented thrombus formation in a dose-dependent manner (median effective dose 0.55 mg/kg). When given to rats with 6-h-old thrombi, sulodexide caused a marked reduction in thrombus size which reached 70% after 2 h with the highest dose tested (2 mg/kg). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 6 publications
5
21
0
1
Order By: Relevance
“…About 40% of the reduction of thrombus was counteracted by preinjection of the antifibrinolytic agent, indicating the fibrinolytic effect of sulodexide (Table III). 11 An increase of the plasminogen acti-vator in the euglobulin activity was demonstrated in these experiments. Administration of fluorescein-labeled sulodexide revealed diffused infiltration of the thrombus with the fluorescent compound, indicating binding as well as antithrombotic and profibrinolytic effects of sulodexide on the thrombus.…”
Section: P H a R M A C O D Y N A M I C S A Anticoagulant And Venous supporting
confidence: 58%
See 1 more Smart Citation
“…About 40% of the reduction of thrombus was counteracted by preinjection of the antifibrinolytic agent, indicating the fibrinolytic effect of sulodexide (Table III). 11 An increase of the plasminogen acti-vator in the euglobulin activity was demonstrated in these experiments. Administration of fluorescein-labeled sulodexide revealed diffused infiltration of the thrombus with the fluorescent compound, indicating binding as well as antithrombotic and profibrinolytic effects of sulodexide on the thrombus.…”
Section: P H a R M A C O D Y N A M I C S A Anticoagulant And Venous supporting
confidence: 58%
“…11 The effect of sulodexide on 6 h-old thrombosis showed a significant reduction in thrombus with increasing doses of sulodexide. 11 To investigate the fibrinolytic effect of sulodexide on preformed thrombosis, ⑀-aminocaproic acid as an antifibrinolytic agent was given to the thrombus-bearing animals immediately before sulodexide. About 40% of the reduction of thrombus was counteracted by preinjection of the antifibrinolytic agent, indicating the fibrinolytic effect of sulodexide (Table III).…”
Section: P H a R M A C O D Y N A M I C S A Anticoagulant And Venous mentioning
confidence: 98%
“…SDX intravenously administered in rats induces acceleration of spontaneous fibrinolysis-thrombolysis of preformed thrombi 33. This property is in accord with an increase in plasminogen activators – TPA and UPA in primates and other animals.…”
Section: Pharmacology Of Sdxsupporting
confidence: 57%
“…In addition to the antithrombotic effects of sulodexide, administration of the compound to animals with preexisting thrombi demonstrates a dose dependent reduction in thrombus size (4). It was suggested that this effect could be attributed to the activation of tissue plasminogenic activator and/or the inhibition of plasminogenic activator 1 (12,20).…”
Section: Pharmacology and Clinical Studies Anticoagulant And Antithromentioning
confidence: 99%